Ovarian Cancer - From Pathogenesis to Treatment 2018
DOI: 10.5772/intechopen.74449
|View full text |Cite
|
Sign up to set email alerts
|

The Past, Present and Future of Diagnostic Imaging in Ovarian Cancer

Abstract: Ovarian cancers (OC) include a group of diseases with variable prognoses. While most conventional imaging techniques rely on the detection of tumour burden and distant spread to identify treatment plans, more emphasis is now being placed on screening for early detection and also for more accurate staging using molecular imaging techniques. It is generally accepted that there are some incremental benefits of using serum CA125 levels coupled with cross-sectional diagnostic imaging to aid in the diagnosis, stagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
(58 reference statements)
0
1
0
2
Order By: Relevance
“…Imaging has two significant roles: the first is the detection of limited disease and all sites of disease in the upper abdomen, and the second is predicting resectability. The most common study is a contrast-enhanced CT scan of the thorax, abdomen, and pelvis [47]. Several investigators have shown that a CT scan underestimates the extent of peritoneal disease [48][49][50].…”
Section: Preoperative Imagingmentioning
confidence: 99%
“…Imaging has two significant roles: the first is the detection of limited disease and all sites of disease in the upper abdomen, and the second is predicting resectability. The most common study is a contrast-enhanced CT scan of the thorax, abdomen, and pelvis [47]. Several investigators have shown that a CT scan underestimates the extent of peritoneal disease [48][49][50].…”
Section: Preoperative Imagingmentioning
confidence: 99%
“…• Ultrasonido El ultrasonido se encuentra dentro de los estudios de primera línea para la evaluación de masas anexiales y el diagnóstico de cáncer de ovario (19). Por lo general, se utilizan tanto el ultrasonido transabdominal (UTA) como el transvaginal (UTV), sin embargo, gracias a una mejor resolución, el UTV ha demostrado superioridad a la hora de estudiar y caracterizar las masas anexiales (5).…”
Section: Estudios De Imagenunclassified
“…Otra ventaja que presenta la RM es su efectividad en tumores ováricos limítrofes o en aquellas pacientes con deseo de fertilidad, ya que evita radiaciones innecesarias que podrían perjudicar un futuro embarazo. En conclusión, el estudio que se utilice va a depender de los protocolos establecidos en cada país, los recursos con los que cuente el paciente o el centro hospitalario, la sospecha de expansión de la enfermedad, la condición del paciente y la disponibilidad del personal calificado (20,21).…”
Section: Estudios De Imagenunclassified
“…Traditional imaging methods, such as transabdominal and transvaginal sonography (Miao et al, 2023), computed tomography (CT) (Kryzhanivska et al, 2023), magnetic resonance imaging (MRI) (Zhang et al, 2017), positron emission tomography (PET) (Li et al, 2023), and color doppler imaging (Wang et al, 2023) are often not sensitive enough to detect ovarian cancer early or to accurately assess the extent of the disease (St Lorenz et al, 2023). Additionally, the technical limitations of these imaging techniques in assessing tumor characteristics and metastasis can lead to misdiagnosis or inaccurate staging (Suppiah, 2018). Furthermore, the high cost of these diagnostics and the absence of a well-defined detection point often lead to delays in diagnosis, further compromising treatment outcomes (Zhang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%